(untitled) (Research, Society and Development, 2021)
According to the World Health Organization, population aging is one of the greatest challenges facing society. The discovery of antimicrobials (ATM) positively transformed clinical practice, however, the WHO highlights the growing emergence of resistant pathogens to these. The present study sought to analyze the use of ATMs in elderly patients hospitalized in a military hospital in Belém-PA, as well as the identification of possible problems related to these. Twelve patients were included in the study, who had a mean hospital stay of 36.6 days and 11 different antimicrobials prescribed. Of these, 89.7% prescriptions had adequate indication, dose in 84.5% and duration of treatment in 55.2%. After analyzing the tracers, it was identified that 3 patients had adverse drug reactions (ADR). The presence of patients with inadequate prescription of TMJ, regarding the indication, dose and duration of treatment, may be related to the absence of adequate therapeutic protocols for their use and administration. Thus, intensive monitoring of TMJ use in the elderly population in a hospital environment is extremely important, seeking to avoid the emergence of ADRs, which are often responsible for the worsening of the clinical condition of these patients and unnecessary expenses. Finally, it is important to highlight those further studies with a larger number of individuals are needed, to prove or not, the inappropriate use of these drugs in this population.